Recruitment and retention of underrepresented and vulnerable populations to research. Issue 6 (8th July 2021) - Langer, Shelby L.; Castro, Felipe González; Chen, Angela Chia‐Chen; Davis, Kelly Cue; Joseph, Rodney P.; Kim, Wonsun (Sunny); Larkey, Linda; Lee, Rebecca E.; Petrov, Megan E.; Reifsnider, Elizabeth; Youngstedt, Shawn D.; Shaibi, Gabriel Q.
Abstract: Per principles outlined in the Belmont Report, research involving human subjects should minimize risks to participants and maximize benefits to participants and society. Recruitment of participants should be equitable. Once enrolled, participants have the right to withdraw at any point. Researchers must balance these principles with pressures to meet enrollment goals and, in the context of repeated‐measures designs, retain participants across time. The purpose of this perspective is to describe the approach and corresponding activities for recruiting and retaining underrepresented and vulnerable populations that are the focus of a transdisciplinary academic research center. To this effort, we offer diverse disciplinary backgrounds, experience working with a wide range of populations (from infants to older adults and across multiple health conditions), and spanning a variety of research designs. Effective strategies offered include partnering with community entities, approaching potential participants where they are and at a time of readiness, using population‐appropriate modes of communication and data collection, conducting study activities in familiar settings and at convenient times, maintaining frequent contact, and offering meaningful incentives. These strategies are consistent with population‐specific reports found in the extant literature and underscore their cross‐cutting nature, with adaptations based on participant and community partner needs and preferences.